Modulation of seminal plasma content in extended semen improves the quality attributes of ram spermatozoa following liquid preservation at 3–5°C. (28th June 2018) - Paul, Rajani K.; Balaganur, Krishnappa; Kumar, Davendra; Naqvi, Syed M. K.
Abstract: Seminal plasma (SP) is known to induce motility and capacitation in spermatozoa curtailing their lifespan when preserved. Hence, this study was conducted to examine the effects of removal of SP from sperm surface prior to liquid preservation either by high dilution (1/15) or by washing and the poststorage treatment with SP (15% and 25%, v/v) on the quality attributes of liquid‐preserved ram semen. Over the period of storage, the rapid motility (66.0% and 71.1% vs. 58.3%), straightness (87.1% and 82.1% vs. 79.4%), average path velocity (152.3 and 152.0 µm/s vs. 133.3 µm/s) and the straight‐line velocity (131.3 and 127.8 µm/s vs. 108.5 µm/s) were significantly ( p < 0.05) higher in both the high‐dilution and wash groups as compared to the control (1/3 dilution). The functional membrane integrity (82.3% vs. 77.2%) and noncapacitated sperm count (65.0% vs. 58.7%) were also significantly ( p < 0.05) higher in the high‐dilution and wash groups, respectively, as compared to the control. The poststorage treatment of sperm with SP significantly ( p < 0.05) increased the functional membrane integrity (70.1% vs. 53.8%) and most of the motility attributes as compared to the control (without SP). In conclusion, both the removal of SP prior to liquid preservation and poststorage treatment with SP significantly improved the quality attributes of ram spermatozoa.